2020
DOI: 10.1002/ldr.3618
|View full text |Cite
|
Sign up to set email alerts
|

Newly created farmland should be artificially ameliorated to sustain agricultural production on the Loess Plateau

Abstract: The farmland area on the Loess Plateau has decreased because of the Grain for Green Programme and other soil conservation measures. The Gullies Reclamation for Farmland Project has been implemented to increase the farmland areas. Many farmlands have been created, but their suitability for Note for his deletion: because of duplication crop production and sustainable management practices is unknown. Topsoil was sampled from 119 sites to evaluate the soil fertility parameters (e.g., SOM, nitrogen, phosphorus, cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The soil nutrient quality evaluation index of 91.8% in the Loess Plateau was in grade I and grade II, and the soil nutrient evaluation index was poor overall. Some studies have also shown that the Loess Plateau belongs to low quality cultivated land, with large topographic fluctuation, a lack of irrigation conditions, poor soil quality and low soil nutrient content [44,45]. The scope of this study was 0 to 60 cm soil layer, and the SQI showed a downward trend as the soil layer decreased, and there were significant differences in the SQI among different layers.…”
Section: Discussionmentioning
confidence: 83%
“…The soil nutrient quality evaluation index of 91.8% in the Loess Plateau was in grade I and grade II, and the soil nutrient evaluation index was poor overall. Some studies have also shown that the Loess Plateau belongs to low quality cultivated land, with large topographic fluctuation, a lack of irrigation conditions, poor soil quality and low soil nutrient content [44,45]. The scope of this study was 0 to 60 cm soil layer, and the SQI showed a downward trend as the soil layer decreased, and there were significant differences in the SQI among different layers.…”
Section: Discussionmentioning
confidence: 83%
“…The MR51 provided the best soil microstructure and sufficient fertility for B. napus , and the roots development of B. napus would promote nutrient transformation (Liu et al, 2020). Hence, the fertility of MR51 exceeded that in NCF cultivated for three years (Ma, Chen, Wang, et al, 2020) (Table 1), and its B. napus growth was significantly higher than most other treatments (Figure 5).…”
Section: Discussionmentioning
confidence: 90%
“…The soil of NCF is mainly dominated by red clay removed from the depth of the surrounding slopes (Ma, Chen, Zhou, et al, 2020). The red clay is compact and cohesive due to the high clay and low sand content, which caused the poor microstructure of NCF (Ma, Chen, Wang, et al, 2020). The uncultivated soil generally has lower concentrations of organic matter, nitrogen, phosphorus, and nutrients, which results in the weak fertility of NCF (Li et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Second, farmers who need cropland for survival have no right to reclaim abandoned cropland derived from off‐farm workers according to China's farmland policies (He et al, 2020; Wang, Li, He, et al, 2020). Finally, at the level of plot, cropland has uneven value following diverse attributes, thereby resulting in irrational farming and vegetation restoration patterns (Ma et al, 2020; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%